Comparison of tubular and planar design of a micro linear generator for vibration energy harvesting - Nor, N.I.M. (Institute of Electrical and Electronics Engineers Inc., 2015)
Vibration sources is available from many appliances such as motors, generators and rotating devices. This vibration can be harvested and converter to electrical energy to power up wireless sensor network and low power electronic devices. An energy harvester is attached to the vibrating source to harvest the energy. The use of micro linear generator comprising of magnet, moving rotor, stator and windings, will enable users to harvest the vibration energy. The generator converts the vibration energy to electrical energy. In this research, a model of a micro linear generator is presented. This paper focuses on comparing a tubular and a planar design of the micro linear generator for vibration energy harvesting. On top of that, the slotted and slot-less designs are also compared. With the Finite Element Analysis (FEA) software, Ansoft Maxwell, the magnetic flux, flux lines, magnetic field and induced voltage of the various designs of the generator are analysed. By evaluating the simulation results, the tubular slotted design is found to be the best design that produced the best output. Â© 2015 IEEE.